Effect of esomeprazole with and without a probiotic on fecal dysbiosis, intestinal inflammation, and fecal short‐chain fatty acid concentrations in healthy dogs - Rae McAtee; Sarah M. Schmid; M. Katherine Tolbert; Scott Hetzel; Jan S. Suchodolski; Jessica C. Pritchard (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Proton pump inhibitors can cause diarrhea and a transient increase in fecal dysbiosis index in dogs. It is unknown if concurrent probiotic administration mitigates these effects. Objective/Hypothesis To assess the fecal Canine Microbial Dysbiosis Index (CMDI), fecal short chain fatty acid (SCFA), and fecal calprotectin concentrations in dogs administered esomeprazole with and without a probiotic. Animals Eleven healthy dogs. Methods Prospective, within‐subjects before and after study. All dogs received 7‐day courses of esomeprazole (1 mg/kg PO q 24h) alone followed by esomeprazole with a probiotic (15 billion CFU/kg), separated by a 4‐week washout period. Data were compared between phases using mixed effects ANOVA or generalized estimating equations with post‐hoc Holm adjustment for 2‐way comparisons. Results Compared to baseline (mean CMDI −2.66, SD 3.04), fecal CMDI was not different with esomeprazole administration alone (mean CMDI −1.48, SD 3.32, P = .08), but there was a significant increase (Diff 3.05, 95% CI [1.37, 4.74], P < .001, Effect size 2.02) when esomeprazole and a probiotic were administered concurrently (mean CMDI 0.39, SD 2.83). CMDI was significantly higher when esomeprazole was administered with a probiotic than alone (Diff 1.87, 95% CI [0.19, 1.87], P = .02, Effect size 1.24). Fecal calprotectin and SCFA concentrations did not differ between phases. The occurrence of vomiting and diarrhea was not different from baseline when esomeprazole was administered alone (36%/27%) or with a probiotic (46%/9%). Conclusions and Clinical Importance In healthy dogs, concurrent administration of a probiotic is unlikely to lessen adverse effects associated with esomeprazole administration.